Seat Choice in a Crowded Café: Effects of Eye Contact, Distance, and Anchoring - Staats, Henk; Groot, Piet (Frontiers in Psychology, 2019)
According to theories of interpersonal distance people choose to position themselves in relation to nearby others in a way that optimizes intimacy and privacy. In two studies we investigated the influence of intimacy and privacy on seating behavior in a café (coffee house) setting. In Study 1 (N=71) we manipulated two aspects of intimacy (eye contact and distance to others), and one aspect of privacy (architectural anchoring) in separate scenario’s and registered participants' seat choice on floor plans of the three hypothetical café’s. We found that more often participants chose a seat that was at a larger distance to other café-goers. Study 2 (N=121) replicated the design of the first study, but included affective and cognitive appraisal measures concerning both available seats in each scenario. This time we found that participants more often chose low-eye contact and anchored seats. Choices in line with hypotheses as well as those that were against hypotheses co-occurred with strong beliefs about the pleasure and arousal that each choice might provide and related to the expectations of interaction with others present. Results qualify expectations about protection and violation of intimacy and privacy, at least for café settings.